Optimal Retail Price Model for Partial Consignment to Multiple Retailers - Po-Yu Chen (Complexity)
This paper investigates the product pricing decision-making problem under a consignment stock policy in a two-level supply chain composed of one supplier and multiple retailers. The effects of the supplier’s wholesale prices and its partial inventory cost absorption of the retail prices of retailers with different market shares are investigated. In the partial product consignment model this paper proposes, the seller and the retailers each absorb part of the inventory costs. This model also provides general solutions for the complete product consignment and the traditional policy that adopts no product consignment. In other words, both the complete consignment and nonconsignment models are extensions of the proposed model (i.e., special cases). Research results indicated that the optimal retail price must be between 1/2 (50%) and 2/3 (66.67%) times the upper limit of the gross profit. This study also explored the results and influence of parameter variations on optimal retail price in the model.